Deaf Children Need Rich Language Input from the Start: Support in Advising Parents - Tom Humphries; Gaurav Mathur; Donna Jo Napoli; Carol Padden; Christian Rathmann (MDPI AG, 2022)
Bilingual bimodalism is a great benefit to deaf children at home and in schooling. Deaf signing children perform better overall than non-signing deaf children, regardless of whether they use a cochlear implant. Raising a deaf child in a speech-only environment can carry cognitive and psycho-social risks that may have lifelong adverse effects. For children born deaf, or who become deaf in early childhood, we recommend comprehensible multimodal language exposure and engagement in joint activity with parents and friends to assure age-appropriate first-language acquisition. Accessible visual language input should begin as close to birth as possible. Hearing parents will need timely and extensive support; thus, we propose that, upon the birth of a deaf child and through the preschool years, among other things, the family needs an adult deaf presence in the home for several hours every day to be a linguistic model, to guide the family in taking sign language lessons, to show the family how to make spoken language accessible to their deaf child, and to be an encouraging liaison to deaf communities. While such a support program will be complicated and challenging to implement, it is far less costly than the harm of linguistic deprivation.